Economics of Golden Crime - Mlčoch, Tomáš (2013)
This master's thesis examines a criminal response to the sharp increase in the real gold price between the years 1998 and 2012. By using a regression analysis, I show that an increase in the real gold price does not have a significant impact on the number of golden crimes but the gold price significantly influences the stolen amount of gold with the elasticity of 2.2. In addition, an increase of lagged real wage and non-lagged real wage, and the number of prisoners significantly decreases golden crime whereas increased unemployment has a negative impact. Moreover, I find that in all types of a regression analysis (daily, monthly and quarterly) higher temperature and also lower cloudiness (as proxies for the good weather) significantly increase the golden crime rate. The daily model also revealed that during weekends and holidays there is significantly and markedly lower crime.